The role of shame and guilt in political violence: from wars and revolutions to genocide and terrorism - Gilligan, James (Interdisciplinary applications of shame/violence theory, 2022)
This chapter is devoted to summarising what has been learned, both by the author and many others studying the same subject, about the causes and prevention of violence. The main thesis is that violence, like all human behaviour and all psychopathology, is multi-determined: the product of the interaction between biological, psychological and social determinants (but in which the social causes are much more powerful than the individual or biological ones). So, this is an interactionist theory, not one that reduces the origin of violence to just one of those categories. But it does propose that there is a phenomenon that is necessary but not sufficient to bring about the causation of violence, just as clearly as the tubercle bacillus is necessary but not sufficient to cause tuberculosis. But it is not a microbe, it is an emotion: namely, the emotion of shame and humiliation—especially in the absence of another opposite and antagonistic emotion that inhibits violent behaviour, namely, guilt and remorse. Researchers from every branch of the behavioural and social sciences have documented how shame and its synonyms are the precipitants of violent behaviour, on both an individual and a collective scale. The most powerful way to reduce the number of citizens who support leaders who resort to shame and authoritarianism, and to reduce the incidence and severity of violence in the population as a whole, would be to decrease the degree of social, economic, political and educational inequality and inferiority, which powerfully shames those who occupy, or fear that they will occupy, lower levels in those status hierarchies.